THE QUILOMBIST APPROACH TO SCIENTIFIC PRODUCTION THROUGH DECOLONIZATION: A BIBLIOGRAPHIC STUDY ON AFROTOURISM (Interdisciplinary Studies Journal, 2025)
:This study aimed to conduct a bibliographic analysis of academic articles on afrotourism, mapping trends, identifying gaps, and understanding the current landscape of scientific production in this context. The methodology used was a bibliographic review, focusing on the selection of articles on afrotourism and afrocentrism in the Redalyc database. During the research, 53 articles were identified, of which 45 were discarded for not directly addressing afrotourism and quilombola communities. The results highlight the need to decolonize knowledge in the field of tourism, breaking away from Western paradigms and marginalization of non-Western perspectives. In this context, the promotion of afrotourism and the strengthening of quilombola communities require strategies for building a more inclusive and anti-racist tourism. The study identified gaps to be addressed, such as the need for intersectional research that explores the complex interactions between race, gender, and other identity dimensions. Expanding the representativity of local communities in academic and practical spheres of the tourism sector is pointed out as an opportunity for future research with a critical, inclusive, and decolonized approach to tourism studies.
Keywords: Afrotourism; Quilombola communities; Decolonization of knowledge; Inclusion in tourism; Cultural representativity